Lebensgeschichten alter Eltern kognitiv beeinträchtigter Menschen Über die biografische Bedeutung des Zusammenlebens mit einem erwachsenen kognitiv beeinträchtigten Kind aus der Perspektive der alten Elternteile - Oermann, Lisa (Perspektiven sonderpädagogischer Forschung, 2023)
It is estimated that 50 -60 % of all adults with learning disabilities in Germany cohabitate with their relatives, mainly with their parents. Regional surveys confirm cohabitation often continues into the fifth decade of the disabled person's lifespan (vgl. Lindmeier et al. 2018). With the aging of the family members, the vulnerability of the family life situation increases. Changes are commonly initiated by the parents' decreasing health, directly affecting the parents ability of care intensity . Until now, science and practice have not developed suitable offers of support. In general, older families are subject to a problem-focused professional discourse and experience themselves confronted with normative regulations. While in the sociological discourse assumptions of normality regarding a family-biography are discussed critically, the work with families with disabled children still assumes a standardized family life cycle as a view on the support structure underlines. Offers of support for older families underestimate the biographical value of their life design and the desire of having this acknowledged, respected and noticed while exploring future perspectives. The presented example of biographical research explores the biographical meanings of living together with an adult disabled child from a parental perspective. The study follows the intention to generate a better understanding and above all appreciation for familiar realities, to support them developing perspectives for their future and to contribute to a new attitude towards older families. In this context family isn't defined as a stable institution (vgl. Fuhs 2002, 23) but as a making in the sense of doing family (vgl. Jurczyk/Lange & Thiessen 2014). In order to portray the diversity of family-life-stories, to reconstruct crisis and strategies of coping, to trace conceptions of 'being family' and to classify the social practice of living together, biographical research is chosen. This appears in the methodology as well as in the epistemological basis of this thesis. On the one hand, biographies are generated in a complex, dialectic interaction of individual acting and social structures. On the other hand, they structure individual acting in turn. Thus, living together can no longer be seen as a sole demonstration of individual action but is likewise socially contextualized. With this approach, the view for the diversity of families with disabled children is enhanced and the long term cohabitation is no longer interpretated as a demonstration of parental failure but as a manifestation of meaningful practice in which society participates at any time. To be able to comprehend the methodic procedure, this thesis starts with a detailed theoretical discussion of its main subjects that are "biography", "family", "older families", "residing/living circumstances" and "age/ageing". In a next step, conferring to the leading issue and the underlying conceptualization of biography, the chosen methods of research are explained. The narrative interview and the biographical case reconstruction according to Gabriele Rosenthal (2014) are eminently suitable to reflect the complex dialectic relation between social structure and individual behaviour inherent to biography. Thus, the thesis attempts to trace and to compare the social phenomenon of living together focusing on the genesis, the maintenance/perpetuation and the transformation, based on three detailed examples of biographies of older parents with disabled children. The presented results form the basis to derive consequences for a different approach to older families and ideas are discussed to adjust and/or reconstruct structures of support. The proposed approaches emphasize disabled people's right to a self-determined life, while they also respect the desire of many families to biographically continue their unique way of 'doing family', hence encouraging a "person and family"-centered planning process to be the future starting point. hence encouraging a "person and family"-centered planning process to be the future starting point.